Precision of fibula positioning guide in mandibular reconstruction with a fibula graft. Issue 1 (December 2016) - Lim, Se-Ho; Kim, Moon-Key; Kang, Sang-Hoon
Abstract Background This study examined the usefulness of the fibula positioning guide for boosting the accuracy of mandible reconstructions. Methods Thirty mandibular rapid prototype (RP) models were allocated to experimental (N = 15) and control (N = 15) groups. For reference, we prepared a reconstructed mandibular RP model with a three-dimensional printer, based on surgical simulation. In the experimental group, a fibula positioning guide template and fibula cutting guide, based on simulation, were used to reconstruct the mandible with a fibula graft. In the control group, only the fibula cutting guide, with reference to the reconstructed RP mandible model, was used to reconstruct the mandible with a fibula graft. The two mandibular reconstructions were compared to the surgical simulation by registering images with the non-surgical right side of the mandible. On the reconstructed side, 3D measurements were compared between the surgical simulation and actual surgery, and the sum of differences was taken as the total error. Results The combined use of the fibula cutting and positioning guides produced a smaller total error (mean ± SD: 10.0 ± 7.9 mm) than the fibula cutting guide alone (12.8 ± 8.8 mm;p = 0.015). The greatest point error was the vertical error at the mesial point of the anterior fibula segment. The anteroposterior and lateral errors were not significantly different between groups. These results showed that these two methods were not significantly different, except in the total and vertical errors. Conclusions Considering the CAD/CAM processes required for creating positioning devices, the benefit provided with a positioning guide justified its use over the fibula cutting guide alone.